Ralf Dahrendorf e l’immagine morale dell’uomo. Ermeneutica della libertà e logica della giustizia sociale - Abbonizio, Giuseppe (SocietàMutamentoPolitica, 2019)
The subject of this essay is social and political liberty, and the nature of the limits that the State and society can be exercised above individuals. With regard to liberty, Dahrendorf carries out two essential operations. First of all, liberty is placed against equality. Then, within a unitary vision of this concept, he shows its fundamental elements, and distinguishes two totally interconnected aspects: the «problematic» concept of liberty and the «assertoric» concept of liberty. According to this hermeneutical hypothesis, i.e. assertoric liberty as a mode of human existence by specific realities behaviour, Dahrendorf defines a form of thinking that is totally separated from the historiography of political liberalism. Furthermore, the principle of social justice is always present in Dahrendorf’s political thought. In this sense, social inclusion is a moral duty, its rational justification is based on a criterion of justice. The process of inclusion of the greatest number of individuals in the sphere of the social contract means adherence to the norms of social coexistence and a condition for the survival of civil society.